2020
DOI: 10.3310/hsdr08010
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and optimising the efficiency of community hospital inpatient care for older people: the MoCHA mixed-methods study

Abstract: Background Community hospitals are small hospitals providing local inpatient and outpatient services. National surveys report that inpatient rehabilitation for older people is a core function but there are large differences in key performance measures. We have investigated these variations in community hospital ward performance. Objectives (1) To measure the relative performance of community hospital wards (studies 1 and 2); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
(115 reference statements)
1
19
0
Order By: Relevance
“…However, alternatives to acute hospitals, such as care homes, special units, hospital-at-home services or community hospitals can, for certain older patients, be safe and possibly lower healthcare costs [ 30 ]. At the same time, neither cost effectiveness nor cost efficiency has been observed in studies comparing community hospitals to acute hospitals in care of older patients [ 31 , 32 ]. As there is a potential to improve outcomes and lower healthcare costs with alternative pathways, we recommend studies with comparable groups for older patients assessed with the decisions system in order to draw conclusions regarding costs and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, alternatives to acute hospitals, such as care homes, special units, hospital-at-home services or community hospitals can, for certain older patients, be safe and possibly lower healthcare costs [ 30 ]. At the same time, neither cost effectiveness nor cost efficiency has been observed in studies comparing community hospitals to acute hospitals in care of older patients [ 31 , 32 ]. As there is a potential to improve outcomes and lower healthcare costs with alternative pathways, we recommend studies with comparable groups for older patients assessed with the decisions system in order to draw conclusions regarding costs and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate care units are an important part of the continuum of services for older people at points of deterioration in health, or when in transition between hospital, home or care home. The provision of palliative care is a commonly cited function of intermediate care units nationally [10] and internationally, but provision varies widely depending on service commissioning and if palliative care is formally recognised in the wider health system [11]. Sezgin et al's systematic review identified these settings as delivering key elements of an effective model of care for older people with multimorbidity [8].…”
Section: Main Findingsmentioning
confidence: 99%
“…Using validated comprehensive outcome measures in routine care is demonstrated to improve detection of unmet needs and individual priorities, provision of the right care at the right time and outcomes of care [41], for example, using the Integrated Palliative care Outcome Scale to assess person-centred comprehensive care needs in routine care [42]. [44].…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations